The Impacts of Covid-19 Pandemy on Technology Literacy Usage on Students Learning Experience - Mezia Kemala Sari; Efri Yoni (Jurnal Sosial Humaniora, 2021)
This study aims at investigating the positive impact of the Covid-19 pandemicwhich has changed the learning process from offline to online. The researchfocuses on the use of the internet as a means of technological literacy which isthe reference for research on student learning experiences. This study uses acomparative descriptive method by comparing internet usage before andduring the pandemic related to the learning process. A structuralquestionnaire link using google form was sent to studentsthrough WhatsApp.A total of 36 students provided complete information regarding the survey.The simple percentage distribution was used to assess the learning status ofthe study participants. The results showed that there was a significantincrease in the use of technology and internet literacy where downloading,uploading, attending workshops, webinars, and online competitions increasedin frequency by using many online learning applications. The positive impactthat can be seen is the increase in digital skills of students and lecturers asshown by their creativity and willingness to be more active, which of coursesupports online learning.